How to stay sane - Perry, Philippa, 1957- (London : Macmillan, 2012)
There is no simple set of instructions that can guarantee sanity, but if you want to overcome emotional difficulties and become happier, psychotherapist Philippa Perry argues that there are four cornerstones to sanity you can influence to bring about change. By developing your self-observation skills, examining how you relate to others, breaking out of your comfort zone and exploring new ways of defining yourself, she demonstrates that it is possible to become a little less tortured and a little more fulfilled. This book is at once a brilliant explanation of our minds and a profoundly useful guide to facing up to the many challenges life throws our way.
Keywords: Gedragstherapieën